1995
DOI: 10.1016/0029-7844(95)00120-g
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Lamellar Body Count: A Rapid and Reliable Fetal Lung Maturity Test

Abstract: The lamellar body count compares favorably with traditional phospholipid testing in the prediction of fetal lung maturity. Phospholipid analysis is not needed with lamellar body counts greater than 30,000/microL or less than 10,000/microL, but may be of benefit for values in the intermediate risk range. Advantages of this test include speed, objectivity, small sample volume required, and universal availability of instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Furthermore, the possible influence was evaluated of other substrates that might contaminate the AF, namely, meconium or blood [15][16][17][18][19][20][21][22][23]. Here again, the experimental data obtained confirmed the behaviour of the conductivity over time as shown in figure 1.…”
Section: Resultssupporting
confidence: 72%
“…Furthermore, the possible influence was evaluated of other substrates that might contaminate the AF, namely, meconium or blood [15][16][17][18][19][20][21][22][23]. Here again, the experimental data obtained confirmed the behaviour of the conductivity over time as shown in figure 1.…”
Section: Resultssupporting
confidence: 72%
“…13 Preterm infants with HMD had lamellar body concentration of less than or equal to 18,000/mL. This finding was lower than that of the studies conducted by Dubin (1989), Bowie (1991) and Dalence (1995) which showed lamellar body concentration of HMD infants of less than 30,000 /mL. This difference might be due to different methods and tools.…”
Section: Discussionmentioning
confidence: 81%
“…This difference might be due to different methods and tools. [14][15][16] We concluded that HMD occurred in 17% of preterm infants. The shake test of gastric and amniotic fluids revealed negative or +1 results whereas lamellar body concentration had value of less than or equal to 18,000/mL.…”
Section: Discussionmentioning
confidence: 99%
“…• Pearlman et al 31 Bowie et al 32 Ashwood et al 33 Fakhoury et al 34 Greenspoon et al 35 Dalence et al 36 Lee et al 37 Dilena determined that the uncentrifuged specimens in their study had lamellar body number density value 8% higher than the centrifuged specimens; this would yield a value for the normalized cutoff of 52,000/uL. limit whatever.…”
mentioning
confidence: 99%